Microporous surface as a new solution for stent surface modification: A review - Imomali H. Kamolov; Dzhamil A. Asadov; Tamara S. Sandodze; Irina E. Chernysheva (ZAO "Consilium Medicum", 2022)
The introduction of coronary stents into clinical practice has reduced repeated patient visits compared with balloon angioplasty alone. Also, drug-eluting stents substantially reduced the restenosis incidence. Therefore, later complications related to the implantation of a stent coated with a cytostatic-containing polymer became more relevant. The mechanism of late stent complications is multifactorial. It is mainly due to the body's response to the prolonged indwelling of the drug carrier polymer on the coronary stent's surface. There is a trend towards the return of polymer-free drug coating technologies, which are implemented through certain modifications of stent surfaces for better drug retention and proper drug distribution. It is mainly achieved using drug depots in various reservoirs: grooves, nanoparticles in the matrix compound, micropores, through and blind micro reservoirs, etc. New promising technologies for crystallizing cytostatic drugs or depositing them in specially designed reservoirs show good preclinical and clinical results, comparable or even superior to approved coronary stents. Micropores as carriers for antiproliferative agents on the stent surface are a promising direction to rejecting the use of polymers in stents.